Maternal undernutrition and the offspring kidney: from fetal to adult life - Mesquita, F.F.; Gontijo, J.A.R.; Boer, P.A. [UNESP] (Associação Brasileira de Divulgação Científica (ABRADIC), 2010)
Maternal dietary protein restriction during pregnancy is associated with low fetal birth weight and leads to renal morphological and physiological changes. Different mechanisms can contribute to this phenotype: exposure to fetal glucocorticoid, alterations in the components of the renin-angiotensin system, apoptosis, and DNA methylation. A low-protein diet during gestation decreases the activity of placental 11ß-hydroxysteroid dehydrogenase, exposing the fetus to glucocorticoids and resetting the hypothalamic-pituitary-adrenal axis in the offspring. The abnormal function/expression of type 1 (AT1R) or type 2 (AT2R) AngII receptors during any period of life may be the consequence or cause of renal adaptation. AT1R is up-regulated, compared with control, on the first day after birth of offspring born to low-protein diet mothers, but this protein appears to be down-regulated by 12 days of age and thereafter. In these offspring, AT2R expression differs from control at 1 day of age, but is also down-regulated thereafter, with low nephron numbers at all ages: from the fetal period, at the end of nephron formation, and during adulthood. However, during adulthood, the glomerular filtration rate is not altered, due to glomerulus and podocyte hypertrophy. Kidney tubule transporters are regulated by physiological mechanisms; Na+/K+-ATPase is inhibited by AngII and, in this model, the down-regulated AngII receptors fail to inhibit Na+/K+-ATPase, leading to increased Na+ reabsorption, contributing to the hypertensive status. We also considered the modulation of pro-apoptotic and anti-apoptotic factors during nephrogenesis, since organogenesis depends upon a tight balance between proliferation, differentiation and cell death.
Keywords: Nephrogenesis; Blood pressure; Angiotensin receptors; Glucocorticoids; Maternal undernutrition